Exercise improves pulmonary fibrosis and neurological symptoms via S100A12 inhibition - Yan Sun; Yan Sun; Meng Li; Meng Li; Jingmin Yuan; Jingmin Yuan; Wenrui Li; Hongli Quan; Yan Li; Zhenjing Kang; Hao Cheng; Hui Ren; et al. (Frontiers in Immunology, 2025)
BackgroundNeurological symptoms are commonly observed in patients with idiopathic pulmonary fibrosis (IPF). However, the underlying mechanisms remain unclear. Although exercise has been shown to improve pulmonary fibrosis and quality of life in IPF patients, its effects on neurological symptoms in this population are not well understood. Furthermore, a robust animal model linking IPF with comorbid neurological symptoms has not yet been fully developed.MethodsTwenty-eight male C57BL/6J mice were divided into four groups: control, bleomycin (BLM), control + exercise, and BLM + exercise. Mice were administered BLM or saline (7.5 mg/kg), and the exercise groups underwent 45 min of treadmill training per day for 28 days. Behavioral tests (open-field test, sucrose preference test, tail suspension test, and forced swimming test) were performed on days 29–33. Histological analysis assessed pulmonary fibrosis, and biomarkers brain-derived neurotrophic factor (BDNF) and c-Fos were detected. Bioinformatics identified genes altered in IPF, exercise, and depression, validated by Western blotting.ResultsBLM induced pulmonary fibrosis and aggravated neurological symptoms. Exercise significantly alleviated these symptoms and reversed the expression of BDNF and c-Fos. Bioinformatics analysis identified 28 genes upregulated in IPF and depression and downregulated by exercise. The S100A12 gene showed reduced expression in both lung and brain tissues in the BLM group and increased expression after exercise. Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment in the Interleukin 17 (IL-17) and Nucleotide-binding Oligomerization Domain (NOD)-like receptor signaling pathways.ConclusionThis study developed a mouse model and suggests that exercise may offer therapeutic benefits for both pulmonary and neurological symptoms in IPF. Shared molecular pathways may guide future therapies targeting both aspects.